2010
DOI: 10.1071/an09124
|View full text |Cite
|
Sign up to set email alerts
|

Development of profitable milk production systems for northern Australia: a field assessment of the productivity of five potential farming systems using farmlets

Abstract: Farmlets, each of 20 cows, were established to field test five milk production systems and provide a learning platform for farmers and researchers in a subtropical environment. The systems were developed through desktop modelling and industry consultation in response to the need for substantial increases in farm milk production following deregulation of the industry. Four of the systems were based on grazing and the continued use of existing farmland resource bases, whereas the fifth comprised a feedlot and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
6
1
Order By: Relevance
“…Potassium surpluses were generally of a similar order to those determined for N. In turn, S surpluses tend to be similar to those determined for P. Very few studies have considered K balances on dairy farms and none appear to have measured S balances. Fangueiro et al (2008) reported K surpluses between 52 and 107 kg K/ha for a range of commercial dairy farms in Northern Portugal, while Chataway et al (2010) found that K surpluses ranged between 22 and 156 kg K/ha in five contrasting farmlets in south-east Queensland; both lower than those determined in this study.…”
Section: Nutrient Balances and Use Efficienciescontrasting
confidence: 47%
See 2 more Smart Citations
“…Potassium surpluses were generally of a similar order to those determined for N. In turn, S surpluses tend to be similar to those determined for P. Very few studies have considered K balances on dairy farms and none appear to have measured S balances. Fangueiro et al (2008) reported K surpluses between 52 and 107 kg K/ha for a range of commercial dairy farms in Northern Portugal, while Chataway et al (2010) found that K surpluses ranged between 22 and 156 kg K/ha in five contrasting farmlets in south-east Queensland; both lower than those determined in this study.…”
Section: Nutrient Balances and Use Efficienciescontrasting
confidence: 47%
“…In a paddock-scale N fertiliser study in south-east Victoria, Eckard et al (2007) reported N surpluses of between 48 and 229 kg N/ha and N-use efficiency between 30 and 50%. In a 4-year farmlet study with differing stocking rates and feed and fertiliser inputs in south-east Queensland, Chataway et al (2010) reported N surpluses between 178 and 600 kg N/ha and use efficiencies between 16 and 25%. In south-west Western Australia, Staines et al (2011) reported N surpluses from a dairy farmlet study, which ranged between 72 and 779 kg N/ha and use efficiencies between 17 and 50%.…”
Section: Nutrient Balances and Use Efficienciesmentioning
confidence: 99%
See 1 more Smart Citation
“…4. Development of the design artefact 4.1 Practical problem context and relevant analysis Decision making in agricultural industries, particularly livestock-based businesses in Queensland, Australia, has been faced with rapid changes due to the effect of climate change, government regulations and changes in farming methods (Chataway et al, 2010), resulting in the disuse of many DSS applications (Kerr, 2004). This disuse was due to the lack of fit to the needs of decision makers' contextual variables.…”
mentioning
confidence: 99%
“…Dairy grazing systems have established their economic sustainability and competitiveness through effective pasture production and usage. Systems that maximize pasture utilization reap benefits in terms of productivity and profitability (Chataway et al, 2010;Ramsbottom et al, 2015), thereby maintaining resilience against market prices and climate threats (Fariña and Chilibroste, 2019). Strategies aimed at increasing the SR directly impact the amount of grass harvested (Baudracco et al, 2011), reducing the milk production costs without compromising homegrown forage production.…”
Section: Introductionmentioning
confidence: 99%